Metal‐free Radical Cyclization of Olefinic 1, 3‐Dicarbonyls and Olefinic Amides with Nitrile C(sp3)−H Bonds in Aqueous Media. Issue 12 (26th October 2021) - Qin, Fu‐Hua; Wang, Hui‐Zhi; Cao, Ting‐Ting; Liu, Qi‐Li; Xu, Qing; Zheng, Hongxing; Zhu, Meiling; Li, Ting; Liu, Yi‐Lin; Wei, Wen‐Ting
Abstract: A radical cyclization of olefinic 1, 3‐dicarbonyls and olefinic amides with nitrile C(sp 3 )−H bonds for the preparation of valuable 2, 3‐dihydrofurans and benzoxazines have been developed. This protocol can be conducted at metal‐ and base‐free conditions in aqueous media with moderate to good yields. Moreover, the practicality of this strategy is further highlighted by gram‐scale reactions. The mechanistic investigation reveals that the transformation is initiated by in‐situ formed cyanomethyl radical. Abstract : A radical cyclization of olefinic 1, 3‐dicarbonyls and olefinic amides with nitrile C(sp 3 )−H bonds for the preparation of valuable 2, 3‐dihydrofurans and benzoxazines has been developed. This protocol can be conducted at metal‐ and base‐free conditions in aqueous media with moderate to good yields.